Aplikasi Optimisasi Penentuan Lokasi Warehouse dengan Runner-Root Algorithm pada PT X - Sanitya Purnomo; Yulia Yulia; Henry Novianus Palit (Jurnal Infra, 2019)
Website-based application that will be created is an optimization application to determine the warehouse leasing location that can help company to find out where the warehouse location is the most optimal with a variety of predetermined parameters. Calculation process to generate the recommendations is using runner-root algorithm. Runner-root algorithm is a numerical optimization algorithm inspired by the strawberry plant for solving continuous multi-variable problems. Stages of analysis and design of record data and company needs are needed to produce good information. Information generated by the application is expected to support the decision-making process by the company.The final result of the development is an optimization application for determining the warehouse leasing location. The developed application has conclusion that applications are more needed in cities that have a large number of customers and alternatives of warehouses. The number of iterations also determine the optimization of the fitness value results.